Placenta accreta : pathophysiology and prenatal ultrasound - binti Ismail, Hamizah (2018)
Placental accreta is a potentially fatal condition. Previous caesarean section and curettage are two major risk factors. Ultrasound and/or magnetic resonance imaging (MRI) are used to make the diagnosis. Placenta praevia, increased thickness, lacunar vacuoles, bulges into the bladder, increased vascularity, and confluent vessels are all ultrasound features.